Value of lung ultrasound scores in assessing extravascular lung water in septic shock patients - Xueyan Zhang; Zhifeng Li (Scientific Reports)
Abstract The aim of this study was to explore the clinical value and accuracy of lung ultrasound in evaluating extravascular lung water (EVLW) in septic shock patients. Twenty-four septic shock patients who required mechanical ventilation and pulse indicating continuous cardiac output (PiCCO) monitoring in the Department of Critical Care Medicine of our hospital were included. Basic laboratory and demographic data for these patients were recorded. PiCCO monitoring was employed to measure EVLW at 0, 2, 6, 12, 24, and 48 h. The lung ultrasound score (LUS) was obtained via bedside transthoracic lung ultrasound (TTE), and the correlation between these two variables was analysed. Of 24 patients, 22 had satisfactory Doppler lung ultrasound results, and a strong correlation was detected between the LUS and EVLW measurements at the 0, 2, 6, 12, 24, and 48 h time points (all P < 0.001; ICC (interclass correlation coefficients) = 0.92, 0.91, 0.92, 0.90, 0.88, 0.71, respectively; all P < 0.001). The Bland‒Altman analysis revealed that only 4 (3.03%) points exceeded the limits of agreement. These findings suggest that pulmonary ultrasound scores can be utilized as an auxiliary metric for identifying EVLW in septic shock patients, suggesting that this technique is well suited for clinical application.